Comparative analysis of the availability and satisfaction of patients with acne with medical assistance in various healthcare facilities - L. O. Golikova; Yu. E. Antonenkov (Кардиоваскулярная терапия и профилактика)
Accessibility and satisfaction with the quality of care for patients with acne are relevant, including in Russia. Therefore, Voronezh Oblast, being one of the largest in the Central Federal District, is able to present these indicators for the whole of Russia. The aim was to compare the accessibility and satisfaction of patients with acne with medical assistance in various healthcare facilities through a survey. The results obtained during the work revealed significant problems in this area and created opportunities for overcoming them.